Restorative urban design: toward a design method for mitigating human impacts on the natural environment through urban re/development - Toros, Tulu (Kansas State University, 2015)
The Restorative Urban Design (RUD) calls for a new urban design and planning approach targeting environmentally responsible re/development of urbanized areas through ecologically responsive impact mitigations. If implemented in a systematic manner, such re/developments can help move urban areas toward the successful restoration of the natural environment of which they are an inseparable part. The RUD model advocates more rigorous assessment and mitigation of urban impacts by carefully evaluating the environmental performance of urban re/developments within five primary dimensions: Atmosphere (emissions, pollutants, ozone depletion); Hydrosphere (stormwater, domestic water, wastewater); Lithosphere (land use, land cover, food and wastes); Ecology (habitat resilience, biodiversity, population and resources); and Energy (renewability, reduction and efficiency, transportation). The model relies on a scenario-comparison process in order to evaluate and optimize the performance of urban re/development projections through four critical scenarios, which are respectively: 1) Natural Baseline (NBASE); 2) Historic Progression (HPROG); 3) Trajectory Forecast (TFORE); and 4) Restorative Projection (RPROJ). The RUD Case Study illustrates how the principles and strategies of Restorative Urban Design can be applied specifically to a typical (densely developed) urban area, namely River North District in Chicago Metropolitan Area. The case study focuses exclusively on mitigation of a single critical human impact on the natural environment: Anthropogenic CO₂ Emissions. The case study focuses on the design assumptions by which the restorative urban re/development scenarios might exceed beyond the full mitigation of emissions into the global remediation by 2040. The restorative projections illustrate that only a certain portion of emissions can be effectively mitigated onsite (5 to 55%), and that the remainder of projected emissions (45 to 95%) need to be mitigated offsite in order to achieve the necessary sequestration and storage. The restorative research suggests that the mitigation of major human impacts on the natural environment – not only CO₂ emissions but also other major impacts – are likely to require significant urban transformations. Moving beyond the strategies of preservation and/or conservation, the restorative approach asserts that comprehensive environmental restoration is achievable if urban impacts are adequately estimated and then entirely mitigated onsite as well as offsite through a systematic process of urban re/development.
Keywords: Sustainable urban design; Sustainable design; Environmental restoration; Ecological restoration; Urban ecology; Urban design; Architecture (0729); Climate Change (0404); Design (0389); Energy (0791); Environmental Health (0470); Environmental Sciences (0768); Environmental Studies (0477); Land Use Planning (0536); Sustainability (0640); Urban Planning (0999); Wildlife Conservation (0284); Wildlife Management (0286)